Análise da relação entre carga planejada pelo treinador e carga experienciada pelo atleta de esportes de combate - Walesko, Francisco (2020)
Combat sports are historically known for their intense and exhausting training and competitions, and the search for improvements in performance, motor quality, technical and tactical aspects are constant. Training loads must remain adequate to avoid an excessive or underestimated state of stress. In this context, most coaches are looking for easy to use, non-invasive and lowcost biofeedback tools. This work aimed to analyze the psychological, physiological responses and relationships between coaches plan and athletes. The sample consisted of 6 coaches and 23 athletes from national and international teams in the modalities of Karate, Judo and MMA, aged 23.9 ± 5.3 years, 13 athletes competing in categories up to 70kg, 8 up to 90kg and 2 in categories over 90kg. During 16 visits, they were monitored with 2 training sessions for each athlete, 7 of which were considered strong (> 5), 7 moderate (3-5) and 2 light (1-2) from a CR10 scale. To analyze the relationships between planning, perceptual responses, heart rate zones and blood lactate, the Chisquare, ANOVA – Tukey and “t” tests were performed, adopting a significance level of p <0.05. As a result, there were significant differences between the planned load and the perceived effort, showing efforts expected by coaches as underestimated. In the sessions perceived as moderate (p <0.05) and strong (p <0.01), the athletes demonstrated greater permanence in the zone of submaximal HR (80 to 90% of Fcmáx). In both situations there were significant increases in blood lactate immediately afterwards, as well as in the period of 10 minutes of recovery when the session was considered strong (p <0.05). In addition, no significant differences were found in blood lactate between sessions considered moderate and strong. In view of the differences found between planned and perceived charges, one of the aspects that may have contributed to the results is the cultural behavior of technicians and coaches when using the ancient philosophy of martial arts, applying training in a generalist way, in this way, we observe that if finds a lack in the individuality of training and control, taking into account the technical, physical, tactical and performance characteristics, thus providing less perceptual variation and a more assertive adjustment in training.